Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Menjual Barang Kena Cukai yang Tidak Ditempel Pita Cukai untuk Diedarkan : Studi Putusan Nomor 492/Pid.Sus/2021/PN.Tjk - Zainal, Ahmad; Hakim, Lukmanul; Ainita, Okta (Universitas Proklamasi 45, 2022)
The act of counterfeiting excise stamps is not too much of a concern in the community because, in general, people are more interested in big problems or big cases such as crime, terrorism, corruption, and so on. As in the United States, it has offered, delivered, sold, or made available for sale excisable goods that are not packaged for retailers, are not attached with excise stamps, or are not affixed with other excise payment signs in the form of 273,162 cigarettes, as referred to in Article 54 of the Law. Law No.39 of 2007 concerning amendments to Law No.11 of 1995 concerning Excise For his actions, the defendant was sentenced to prison and a fine of twice the excise value. The research method in this paper uses normative and empirical legal research, which is one type of legal research, namely by examining library materials or secondary data of a legal nature. At trial, the panel of judges did not find anything that could absolve the defendant of criminal liability, either as a justification or an excuse, so the defendant must be held accountable for his actions. Because the defendant is capable of being responsible, he must be found guilty and sentenced.